DEVELOPMENT OF THE BONEN CAVE TOURISM AUGMENTED REALITY APPLICATION BASED ON WATERFALL ANALYSIS - Robertho Kadji; Irene Augusta Boymau; Lidia Paskalia Nipu; Ika FitriKrisnasiwi; Henda V. R. Taopan; Frengky S. Banunaek; Rizhard A. Ndolu (RADJA PUBLIKA, 2025)
This study presents the application of an Augmented Reality (AR)–based digital interpretation system to enhance speleological geotourism experiences at Bonen Cave, Baumata Village, Kupang Regency, Indonesia. The research addresses limitations in conventional geotourism interpretation, including low interactivity, limited informational accessibility, and potential environmental disturbance in karst cave environments. The developed AR application integrates three-dimensional cave models, geological explanations, and historical narratives related to the use of the cave during the Japanese occupation period. Implementation was conducted through a community-based approach involving local tour guides and tourism stakeholders. The application was officially launched during the Fatusuba Festival on 17 October 2025 and publicly demonstrated to visitors. Field testing confirmed stable performance and compatibility across multiple Android devices, including Redmi Note 13 Pro, Redmi Note 9 Pro, and Samsung Galaxy A56. Results indicate that the AR application improves visitor engagement, supports knowledge transfer, and strengthens digital promotion of speleological geotourism while reducing the need for direct physical interaction with sensitive cave features. This study demonstrates that AR technology can serve as an effective and sustainable tool for enhancing geotourism experiences and empowering local communities in karst regions.